PENGEMBANGAN PENYUBUR RAMBUT MENGGUNAKAN KOMBINASI EKSTRAK ETANOL HERBA PEGAGAN (Centella Asiatica (L) Urban) DAN EKSTRAK N-HEKSANA BAWANG PUTIH (Allium Sativum L) - Dwi Setyoningsih; Shelly Taurhesia; Teti Indrawati (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
Centella asiatica contains asiaticoside, flavonoid, phytosterol, madecassid acid, madecassoside, Asiatic acid and amino acid which are potentially stimulating hair growth, while Allium sativum has rich nutrient for hair growth such as alkaloid and sterol/terpenoid. Objective: previous study showed each extract has activity to stimulate hair growth but there was no study yet for a combination of these two extracts. The objective of this study was to find right concentration for combination of gotu kola herb extract and garlic extract which can stimulate hair growth, and the best combination will be then formulated into hair tonic and test its activity. Methods: Application on 3 male rabbits for 28 days of combination of 1.25% gotu kola herb extract and 100 ppm garlic extract showed hair growth of 34.10 mm, hair growth acceleration 1.388 mm /day and hair weight 27.816 mg. Then Hair tonic was developed using three different formulas, namely F1 contains of 2.5% gotu kola herb extract and 0.02% garlic extract; F2 contains of 2,5% gotu kola herb extract and 0.04% garlic extract and F3 contains of gotu kola herb extract 5% and garlic extract 0.04%. This hair tonic has green color, distinctive odor, homogeneity, a viscosity of 2.629 cP to distilled water, and pH 5.6. The results showed that Hair tonic of F3 with a concentration of 5% gotu kola herb extract and 0,04% garlic extract gave hair growth of 28,62 mm, rate of hair growth of 1,057 mm/day and hair weight of 28,84 mg, and this hair tonic is stable for 3 months storage at 25oC as well as at 40oC.